NUMBER AND TIME OF WEEDING EFFECTS ON MAIZE GRAIN YIELD - SILVA, PAULO SÉRGIO LIMA E; MESQUITA, SORIEUDES SANTOS XAVIER; ANTÔNIO, RAFAELA PRISCILA; SILVA, PAULO IGOR BARBOSA E (International Journal of Maize & Sorghum, 2010)
Several problems are to blame for the low yields of maize in the State of Rio Grande do Norte, Brazil. Among these problems, the lack of weed control in the proper season is one of the biggest. The experiment was conducted in Mossoró-RN, in a sprinkler-irrigated area. The objective of this work was to evaluate the influence of one weeding (at 15, 30, 45 or 60 days after planting, DAP), two weedings (15 and 30, 15 and 45, 15 and 60, 30 and 45, 30 and 60 or 45 and 60 DAP), three weedings (15, 30 and 45; 15, 30 and 60 or 30, 45 and 60 DAP) or four weedings (15, 30, 45 and 60 DAP) on cultivar Centralmex grain yield. A “no weeding” treatment was also included. A random block design with four replicates was utilized. The lack of weeding reduced plant and ear heights, as well as grain yield and its components. The highest grain yields were obtained with treatments 30 DAP, 15-30 DAP, 30-45 DAP, 30-45-60 DAP, and 15-30-45-60 DAP. Greater net revenue with grain commercialization can be obtained with treatment 15-30 DAP.